Chronic obstructive pulmonary disease and the risk of stroke: a systematic review protocol - Jennifer K Quint; Ann D Morgan; Chetna Sharma; Kieran J Rothnie (BMJ Open)
Introduction There is good evidence to suggest that chronic obstructive pulmonary disease (COPD) increases the risk of ischaemic heart disease, in particular myocardial infarction (MI). The relationship between stroke and COPD, however, is not as well established, and studies conducted to date have generated conflicting results.Methods and analysis MEDLINE and Embase will be searched for relevant articles using a prespecified search strategy. We will target observational studies conducted in the general population that employ either a longitudinal cohort or case–control study design to estimate ORs, HRs or incident rate ratios for the association between COPD and a subsequent first stroke. Both stages of screening, title and abstract followed by full-text screening, will be conducted independently by two reviewers. The Population, Exposure, Comparator, Outcomes, Study characteristics (PECOS) framework will be used to systematise the process of extracting data from those studies meeting our selection criteria. Study quality will be assessed using an adapted version of the Newcastle-Ottawa risk of bias tool. The data extraction and the risk of bias assessment will also be conducted in duplicate. A meta-analysis will be considered if there is sufficient homogeneity across selected studies or groups of studies. If a meta-analysis is not justified, a narrative synthesis will be conducted. Selected Grading of Recommendations, Assessment, Development and Evaluation (GRADE) criteria will be used to assess the quality of the cumulative evidence.Dissemination Currently ranking second and fourth in the list of global causes of mortality, respectively, stroke and COPD are important non-communicable diseases. With this review, we hope to clarify some of the current uncertainty that surrounds the COPD–stroke relationship and in turn improve understanding of the nature of the role of COPD in comorbid stroke.Prospero registration number CRD42016035932.